Denotative Linguistic Oppositions And Their Doctrinal Dimensions In Arabic Texts: An Applied Study On The Meccan Surat Al-Duha - Hussain, Shaima Muhammad Tawfeeq Mulla (Ijaz Arabi Journal of Arabic Learning, 2025)
This research examines the denotative linguistic oppositions and their doctrinal dimensions in Arabic texts. It is applied on the Meccan Surat Al-Duha. This topic emerges from the linguistic differentiation of its types and doctrinal dimensions by inserting the word and its opposite, mentioning the factor deleting its direct object, and mediating between the word and what it asks for. In the case of oath, the condition is mediated between its elements; in the superlative style, the description is mediated between the preferred and the preferred upon, while in the negative style, the subject is mediated between its events. It presents a linguistic, semantic, rhetorical, and doctrinal analysis of the methods of denotative linguistic oppositions in the Arabic text, combining the rules of Arabic grammar, the methods of Arabic rhetoric, and the purposes of faith, highlighting the apparent commonness with its dimensions and types under study. This study adopts a qualitative analytical approach based on descriptive and interpretive methods. The analysis is rooted in both linguistic and rhetorical examination of Surat Al-Duha, supported by classical and modern Qur’anic exegesis (tafsir). The analytical linguistic, semantic, doctrinal, and initiative approach was inspired by it, leading to the occurrence of denotative linguistic correspondence with its doctrinal dimensions in Arabic texts in a single verbal manner and a definite syntactic manner in the two types of declarative and constructional linguistic styles, with what it entails in the style of oath, negation, interrogative, prohibition, and command. This study recommends dealing with linguistic texts in the light of denotative linguistic oppositions, with their various doctrinal dimensions, as a type of metasynthetic analysis. The analysis transforms the structure according to the many grammatical, rhetorical, and doctrinal meanings they indicate within the limits of what the text permits and accepts in a linguistic setting and an authentic interpretive law.